2021
DOI: 10.7717/peerj.10627
|View full text |Cite
|
Sign up to set email alerts
|

Luzindole and 4P-PDOT block the effect of melatonin on bovine granulosa cell apoptosis and cell cycle depending on its concentration

Abstract: Granulosa cells play an essential physiological role in mediating the follicle development and survival or apoptosis of granulosa cells dictate the follicle development or atresia. The aim of this study was to investigate the role of high dose (10−5 M) and low dose (10−9 M) melatonin in bovine granulosa cells, and assess whether MT1 and MT2 inhibiter affect granulosa cells response to melatonin. We found that the high dose (10−5 M) and low dose (10−9 M) both could act as an essential role in modulating granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Researchers have shown that the two MSI proteins play critical roles in the proliferation and differentiation of stem cells of the hematopoietic and nervous systems 121,122 . Nonetheless, Wang and al., 2021 confirmed that MT2 inactivation in bovine GC by 4P-PDOT may affect the regulatory action of melatonin on GC functions 123 .…”
Section: Effects Of Mt2 Receptor Activation or Inhibition On Human Gc...mentioning
confidence: 85%
“…Researchers have shown that the two MSI proteins play critical roles in the proliferation and differentiation of stem cells of the hematopoietic and nervous systems 121,122 . Nonetheless, Wang and al., 2021 confirmed that MT2 inactivation in bovine GC by 4P-PDOT may affect the regulatory action of melatonin on GC functions 123 .…”
Section: Effects Of Mt2 Receptor Activation or Inhibition On Human Gc...mentioning
confidence: 85%
“…Although MT2 activation promotes apoptosis under BL-induced stress, our current data indicate that MT2 induction protects corneal epithelial cells from impaired autophagy and ROS stress. Many previous studies have demonstrated that apoptosis is an important pathway that protects cells from damage, as the balance between BCL2 and BAX can protect mitochondrial function and proliferation in normal cells and other tissues [ 4 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MLT receptors are expressed in the ovaries of various mammals, including sheep and that the function of MLT in mammalian ovaries is mainly mediated by MT1 and MT2 (He, Deng, et al, 2016; Lee et al, 2018; Tian et al, 2017; Yang et al, 2017). It has also been suggested that the MT1 receptor and EGF/EGFR‐mediated signaling pathway may interact significantly during cell proliferation because the MT1 receptor activates MLT antiproliferation signaling by mediating EGF/EGFR signaling (Wang et al, 2021). However, there are some differences between the results of these studies and our results, which may be attributed to different types and sources of melatonin and the fact that there are species differences in the response of granulosa cells to EGF (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%